Aviva vs. the dybbuk - Lowe, Mari (Levine Querido, 2022)
Eleven-year-old Aviva Jacobs and her mother are grieving the loss of Aviva's father who died in an accident in the town of Beacon. After moving into an apartment above a mikvah, a ritual pool maintained by her mother, Aviva begins seeing a dybbuk--a mischievous spirit in the form of a boy--who causes trouble around her home and Jewish community. While Aviva tries to manage the dybbuk's antics, she gets placed in charge of planning a bat mitzvah celebration with her ex-best friend, Kayla. Working together doesn't seem to alleviate the tension between the former friends, and it only gets worse when an act of anti-Semitic vandalism at their synagogue puts the community on high alert.